The significance of including the lived experiences of African Americans in adult basic education curriculum and planning - Vanessa Sheared (Adult Education Research Conference, 1995)
The need to connect education and learning to the "lived experience" of adults has been discussed as a goal within adult education. One hundred fifty three interviews were conducted with African American adult students, administrators, and educators in the state of California. This study suggests that African Americans will participate and do participate in those programs that connect with their culture and life stories – their lived experiences.